European Insurance Markets in Face of Financial Crisis: Application of Learning Curve Concept as a Tool of Insurance Products Innovation â€“ Discussion - Sliwnski, Adam; Karmanska, Anna; Michalski, Tomasz (Journal of Reviews on Global Economics, 2017)
The paper aims to present the results of an assessment of development of insurance sector in chosen European countries like Poland, UK, Germany and France over the financial crisis especially from product’s innovation point of view. The comparison between the level of taxonomic measures in two points in time let the Authors to write main conclusion that insurance markets have been not so innovative in chosen countries. The level of innovations have been especially law in terms of insurance offer (Products). The first part of the paper ends with a short description of so called new risks that impose a level of innovations within an insurance sector. The second part contains a discussion about possibility of using learning curve concept for the process of insurance product innovation especially products â€œwithout claims historyâ€.